Penggunaan Paket Literasi Untuk Stimulasi Kemampuan Literasi Anak Usia Pra-Sekolah - INDRIANI, ALFIANA (2016)
THE USE OF THE LITERACY PACKAGE TO STIMULATE THE LITERACY ABILITY OF THE PRESCHOOL-AGE CHILDREN Alfiana Indriani Dr. Lisnawati Ruhaena, M.Si, Psi Indriani.Alfiana@gmail.com Psychology Faculty, Muhammadiyah University of Surakarta ABSTRACT The literacy stimulation package given to the mothers through the previous research gave benefits in increasing the mothers' knowledge and perception in giving the literacy stimulation package to the preschool-age children. Besides, the literacy stimulation package given was also useful in increasing the abilities in reading, writing, coloring, and skills. It was the base of the objective of this research which was to understand about how the use of the literacy stimulation package conducted by the mothers to the children was. Informants in this research were parents of children of 3-5 years old who used the literacy stimulation package and had domicile in Surakarta. The amount of Informants in this research was 6 Informants. The use of the literacy package for the literacy stimulation of the preschool-age children in this research would be discovered using the methods of interview, observation, and daily notes by finding information related to the mothers's knowledge in the literacy stimulation, the mothers' perception on the literacy stimulation package, the way of using the literacy stimulation package, obstacles faced during the use of the literacy stimulation package, they way to solve the obstacles during the use of the literacy stimulation package, and the results reached from the use of the literacy stimulation package. All results of the analysis and the discussion previously conveyed could be concluded that the use of the literacy stimulation package by the mothers to the children gave result that by the presence of the literacy stimulation package, the Informants used the literacy stimulation package together by involving an interaction between the mothers and the children in studying the package. Medium in the literacy stimulation package which was often used was the use of story books, and the methods of giving the literacy stimulation package which were often used were the method of story and the method of discussion. The giving of the literacy stimulation package was conducted minimally once every two days. Through the package that had been given, the Informants still felt difficult that was in inviting the children to concentrate and focus on the package they learned together, and the children preferred playing or watching television. The difficulties were solved by the Informants by following everything the children wanted to do and after that, the children were invited to learn again. keywords: The use of the literacy stimulation package, Preschool-Age Children